False, because if a=2 and b=3 then (2+3)^2=5^2=25, which clearly does not equal 2^2+3^2=13.
2007-05-31 13:08:56
·
answer #1
·
answered by bruinfan 7
·
0⤊
0⤋
False-- (1+2)^2 = 3^2 = 9; 1^2 + 2^2 = 1+4 = 5.
theres no way to explain it beyond giving a counterexample... it just isn't true.
2007-05-31 13:08:26
·
answer #2
·
answered by emp211 3
·
0⤊
0⤋
Its false. Think of it like this..........
if a = 2 and b =3 then
(2+3)^2 =25
2^2 +3^2 =13
Those are definately not equal and you can use other numbers in place of a and b.
An old teacher I once had said that the sum of the squares was not equal to the square of the sum and that simple rule applies here
CD
2007-05-31 13:18:20
·
answer #3
·
answered by Celestial Dragon 3
·
0⤊
0⤋
False, foil, a^2 + 2ab + b^2
2007-05-31 13:08:27
·
answer #4
·
answered by richardwptljc 6
·
0⤊
0⤋
It´s false because when you multiply a binomium, you have to multiply each term of the first one with each one of the second and you get a trinomuim. In Spanish it´s called trinomio cuadrado perfecto (something like perfect square trinomius, I dón´t know it´s name in English.
(a+b)^2= (a+b)(a+b)= (a)(a)+(a)(b)+(a)(b)+(b)(b)
=a^2+2ab+b^2
2007-05-31 13:15:44
·
answer #5
·
answered by anacnorisis 2
·
0⤊
0⤋
false It is a^2 +2ab+b^2
2007-05-31 13:09:28
·
answer #6
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
False.
(a+b)*(a+b) = a^2 + 2ab + b^2
a^2 + b^2 = (a-b)^2
2007-05-31 13:12:15
·
answer #7
·
answered by Doug r 2
·
0⤊
0⤋
This is false:
(a+b)^2 = a^2 + 2ab + b^2 (use FOIL method)
This answer D.N.E. a^2 + b^2
2007-05-31 13:09:40
·
answer #8
·
answered by Dara D 1
·
0⤊
0⤋
True.
distributive property.
i cant really explain beyond that.
2007-05-31 13:08:41
·
answer #9
·
answered by Brian M 3
·
0⤊
1⤋
NERDS
2007-05-31 13:17:26
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋